Statistical Physics I : Equilibrium Statistical Mechanics - Toda, Morikazu (Springer series in solid-state sciences, 1992)
Statistical Physics I discusses the fundamentals of equilibrium statistical mechanics, focusing on basic physical aspects. No previous knowledge of thermodynamics or the molecular theory of gases is assumed. Illustrative examples based on simple materials and photon systems elucidate the central ideas and methods.